PENGARUH EFEKTIVITAS PENGENDALIAN INTERNAL, KESESUAIAN KOMPENSASI, ASIMETRI INFORMASI, DAN MORALITAS MANAJEMEN TERHADAP PERILAKU TIDAK ETIS DAN KECENDERUNGAN KECURANGAN AKUNTANSI (Studi Pada Perusahaan Perbankan Di Kota Bengkulu) - Mirra Sri Wahyuni; Helmarini Helmarini (Universitas Muhammadiyah Bengkulu, 2020)
ABSTRACTThe study aims to determine the effect of effectiveness of internal control, compensation compatibility, information asymmetry, and morality of management to unethical behavior and tendency of fraud accounting (study on banking companies in Bengkulu city). The data used in this research is primary data, obtained by distributing questionnaires to the respondents. Total sampel used for this study are 50 sampels. The data was analyzed by using SmartPLS 2.0 M3.The results prove that effectiveness of internal control, compensation compatibility, and morality of management have negative effect on unethical behavior. Effectiveness of internal control, compensation compatibility, and morality of management have negative effect on tendency of fraud accounting, but information asymmetry has no effect on unethical behavior and tendency of fraud accounting. Unethical behavior has positive effect on tendency of fraud accounting.Â Keywords: Effectiveness of Internal Control, Compensation Compatibility, Information Asymmetry, Morality of Management, Unethical Behavior, Tendency of Fraud AccountingÂ